Exercise-induced bronchodilatation in asthmatic athletes - Todaro, A. (The Journal of Sports Medicine and Physical Fitness, 1996)
In most asthmatics muscular effort induces bronchial spasms. However, despite this limitation many of them carry on sports activities even at a high level. It has already been shown that training reduces the bronchial obstruction response while heightening a bronchodilator response. The purpose of this study is to monitor these changes in bronchial calibre under effort condition. To this aim, 14 high-level athletes effected by asthma with chronic bronchial obstruction, but clinically silent, were studied. Under the maximal effort test these athletes displayed very high peak ventilation and peak oxygen uptake. At the end of the effort bronchodilatation was found to occur in all of them, and during recovery a slow return of bronchial patency toward the basal values was noticed: in no case was there any aggravation of bronchial obstruction. It is surely this persistent bronchodilatation that makes it possible for these athletes to achieve high ventilation levels and to carry on sports activities without any respiratory-related limitation. The inhalation of salbutamol before the effort test increases tha amount of bronchodilatation over that already measured during the test without administering the drug. It can be supposed that in these athletes an increase in the number or density of the adrenergic betareceptors occurs, thus promoting the action of the catecholamines. The increase in bronchial calibre that is found under effort, without the use of salbutamol, is such that any prophylaxis using bronchodilator drugs would be hardly useful under favorable climatic conditions.